Regulation and Banking after the Crisis - Morten Balling; Ernest Gnan; Patrick Honohan; David T. Llewellyn; Nigel Jenkinson; Aerdt Houben; Jan Kakes; Pat Farrell; Patricia Jackson; Edward J. Kane; Alistair Milne (SUERF - The European Money and Finance Forum, 2011)
The Central Bank of Ireland and SUERF organised a joint conference in Dublin on 20th September, 2010 on the general theme of Regulation and Banking after the Crisis. In the best traditions of SUERF, the programme included papers and presentations from the three main constituencies of SUERF: Central Banks (including notably the Governor of the Central Bank of Ireland), academics, and financial practitioners. As always, the papers illuminated some of the different perspectives of the three constituencies. We are grateful to the many distinguished contributors who were prepared to make powerful contributions to the conference.
Keywords: C3; E4; E5; F3; G2; 330; banking; bank business models; eurozone; intervention strategies; Ireland; OAD; regulation; risk management; securisation; supervision; systemic risk; too big to fail; Finanzkrise; Ansteckungseffekt; Bankenregulierung; Finanzmarktregulierung; Welt